MOTIVATION OF EDUCATIONAL AND RESEARCH WORK IN PERSONALITY-ORIENTED LEARNING (Pedagogy of Higher and Secondary Education, 2004)
The article shows the role o f motivation as a basic factor of student's readiness to teaching and research activity, singles out groups of motives of scientific-reseat work, outlines some ways of step-by-step purposeful development o f motives of teaching-research work, with the object of raising of effectiveness of readiness to this type of activity under conditions of personal oriented training.